Histological Study of Molar Pregnancy by using some of the Special Stains - Sharef, Tuqa Yousif; Tawfiq, Prshang; Chkhaim, Toqa J (Diyala Journal of Medicine, 2019)
Background: Molar pregnancy (hydatidiform mole HM) is an abnormal form of pregnancy in which a non-viable fertilized egg implants in the uterus and will fail to come to term. A molar pregnancy is a gestational trophoblastic disease which grows into a mass in the uterus that has swollen chorionic villi. These villi grow in clusters that resemble grapes. A molar pregnancy can develop when a fertilized egg does not contain an original maternal nucleus. The diagnosis of HM is based on its morphology. In classic cases, the abnormally large villi have a vesicular or a grape like appearance. Histologically, HM presents variable degrees of circumferential trophoblastic hyperplasia and epithelial atypia. Distinguish between complete mole (CM) and partial mole (PM) is difficult especially with early diagnosis and evacuation of molar pregnancies, however, the criteria are subjective and show considerable inter-observer variability. Unfortunately in our country the histological diagnosis is depend only on routine stain (H&E) which is not giving a clear results in some cases because of that, the study design to find the similarities and differences between the two types of molar pregnancy by using some of special stains which surely distinguish between complete and partial moles samples using immunohistochemical marker P57KIP2. Objective: To detecting if the special stain can be helpful to distinguish between the two types of molar pregnancy also to find the accuracy of the routine diagnosis of hydatidiform mole comparing with P57 immunohistochemistry stain. Patients and Methods: The study conducted at the maternal teaching hospital in Erbil city. Thirty cases of Molar Pregnancy diagnosed, 15 of them were complete and the others were partial mole. All the samples studied histologically using H&E and some of special stains including: PAS stain, Congo red, and Trichrom, to describe the morphological differences between the two types of mole. Also immunohistological P57 stain was used in this study to confirm the type of mole. Results: The study result shows the morphological variation between complete and partial hydatidiform through using the routine H&E stain and special stains. The complete hydatidiform mole sections showed vesicular swelling of chorionic villi and circumferential trophoblastic hyperplasia, the trophoblastic proliferation grade varying in complete samples, most samples showed grade II (46.6%) of trophoblastic proliferation, while few of samples showed grade III (13.3%). The cases of partial hydatidiform mole showed scattered hydropic villi with irregular scalloped villous outlines and mild trophoblastic hyperplasia, trophoblastic distribution elucidate that the majority (60%) of samples show zonal distribution and high percentage (73.3%) of focal trophoblastic proliferation. The vessels in the villous stroma of most of partial molar samples (80%) was obviously seen also the cistern appear clearly in 73.33% of the samples and all partial molar pregnancy samples showed presence of fetal part in contrast to complete mole. The PAS stain show no different between the two types of molar pregnancy samples while the Congo red stained the partial molar samples intensely comparing with complete samples opposite to the trichrome stain which showed highly color intensity in complete than in partial samples. In this study the most important noticed results was high percentage (26.66) of positive result of P57 in complete diagnosed sample by routine way. Conclusion: The special stains can be helpful in diagnosis of hydatidiform mole and The study of p57 immunohistochemistry stain indicate present of misread in routine diagnoses of complete hydatidiform due to mimic morphological characters.